The Effect Of Mobile Legend Of Social Interaction - Nailal Muna; Mohammad Kanzunnudin; Erik Aditia Ismaya (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
This study aims to examine the impact of the online game Mobile Legends on the social interactions of fifth-grade students at SD 1 Mijen Kudus. The method used is qualitative with a descriptive approach. The subjects of the study are fifth-grade students and their teachers. Data collection was conducted through observations, interviews, and documentation. The data analysis technique includes data reduction, data presentation, and drawing conclusions. The results show that students are generally accustomed to using smartphones or gadgets to play online games. The impact of online games greatly depends on their usage; excessive use can lead to addiction, disrupting various aspects of children's lives, but wise use can be beneficial and develop important skills in the digital era. The characteristics of children playing online games reveal that some students often use inappropriate language at school, likely influenced by unsupervised gadget use. The school's follow-up action is to implement policies restricting gadget use to enhance social interaction and focus on learning through a non-violent disciplinary approach. Educators are advised to pay more attention to children who lack social interaction, provide encouragement, and counsel on the importance of making friends. Additionally, teachers should frequently organize activities that involve student collaboration and enforce stricter rules regarding students bringing gadgets to school.